Analysis of the Ratio Decidendi in the Distribution of Marital Property - Felicia Felicia; Mella Ismelina Farma Rahayu (Jurnal Daulat Hukum, 2026)
This study aims to analyze the legal status of joint property that has not been divided after divorce when one of the parties passes away, as well as to examine the judge’s ratio decidendi in Decision No. 520/Pdt.G/2022/PN.DPS concerning the distribution of joint property and inheritance. The research method used is normative juridical research with statutory, conceptual, and case approaches. Legal materials were obtained through library research and analyzed qualitatively using legal interpretation methods. The novelty of this study lies in the analysis of the relationship between the distribution of joint property after divorce and the distribution of inheritance in childless marriages, particularly when the joint property has not been separated before one party dies. Based on the results of the study, it is concluded that joint property must first be separated before the inheritance distribution is carried out. The analysis of Decision No. 520/Pdt.G/2022/PN.DPS shows that the judges recognized the existence of joint property and the rights of the second ex-wife; however, the direct division into two portions was not fully in accordance with the legal construction of the Civil Code because the joint property should first have been separated, after which the deceased’s share should have been proportionally distributed among the heirs in order to ensure legal certainty and justice for the parties.